PP.43 Perinatal Outcomes and Travel Time to Maternity Services: Analysis of Birth Outcome Data in Wales from 1995 to 2009. (26th April 2013) - Paranjothy, S; Watkins, WJ; Rolfe, K; Gong, Y; Adappa, R; Dunstan, F; Kotecha, S
Abstract : Objective: To study the association between travel time from home to hospital on intrapartum stillbirth and neonatal mortality. Population: All births to women who were resident in Wales between 1995 – 2009 (n = 498, 052). Outcome Measures: Intrapartum stillbirth, early and late neonatal mortality. Methods: We calculated the travel time to all hospitals with maternity services based on the grid reference for postcode of mother's place of residence at the time of birth. We used logistic regression to obtain odds ratios for the association between travel time and outcome, adjusted for maternal age, parity, Townsend score for social deprivation and urban/rural location. Results: There were 412, 827 singleton births during the study period. The intrapartum stillbirth rate was 0.3 per 1, 000 (n = 135); early neonatal death rate 1.5 per 1, 000 (n = 609) and late neonatal death rate 0.6 per 1, 000 (n = 251). The median travel time to place of birth was 17 minutes IQR (11, 27), and the median distance travelled was 11.7 km. The risk of early neonatal death increased with travel time of at least 45 minutes to place of birth (adjusted OR 1.7 95%CI 1.2, 2.3). In order to explore whether or not birth outcomes were associated with location of maternity services we repeated the analysis using travel time from home to nearest hospital with maternity services and found no association. Conclusion: Although the risk of adverse birth outcomes is increased with longer travel times to the place of birth this is not explained by distance to the nearest hospital with maternity services.